Advancing Parkinson’S Diagnosis: Seed Amplification Assay for α-synuclein Detection in Minimally Invasive Samples - Chana-Cuevas, P (Springer, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by tremor, rigidity, and bradykinesia, beginning with early loss of dopaminergic neurons in the ventrolateral substantia nigra and advancing to broader neurodegeneration in the midbrain. The clinical heterogeneity of PD and the lack of specific diagnostic tests present significant challenges, highlighting the need for reliable biomarkers for early diagnosis. Alpha-synuclein (α-Syn), a protein aggregating into Lewy bodies and neurites in PD patients, has emerged as a key biomarker due to its central role in PD pathophysiology and potential to reflect pathological processes. Additionally, α-Syn allows earlier differentiation between PD and other neurodegenerative disorders with similar symptoms. Currently, detection of α-Syn pathology in post-mortem brain tissue remains the primary means of achieving a conclusive diagnosis, often revealing significant misdiagnoses. Seed amplification assay (SAA), initially developed for prion diseases, has been adapted to detect α-Syn aggregates in cerebrospinal fluid, showing promise for early diagnosis. Recent studies have demonstrated that SAA can also detect α-Syn aggregates in peripheral samples collected via minimally invasive procedures, such as skin, olfactory mucosa, saliva, and blood. However, the lack of standardized protocols limits clinical application. Standardizing protocols is essential to improve assay reliability and enable accurate patient identification for emerging therapies. This review examines studies on SAA for detecting α-Syn aggregates in minimally invasive samples, focusing on sample collection, processing, and reaction conditions. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.